Insight into the differences in classification of mediastinal and hilar lymph nodes between Wang’s lymph node map and the International Association for the Study of Lung Cancer lymph node map - Li, Ya-Qing; Wang, Ko-Pen; Ben, Su-Qin (Journal of Thoracic Disease; Vol 7, Supplement 4 (December 20, 2015): Journal of Thoracic Disease (The Past, Current and Future Development of High Technology Applied in Thoracic Diseases), 2015)
Lung cancer is the leading cause of malignant-tumor-related morbidity and mortality worldwide. Transbronchial needle aspiration (TBNA) has for the past 30 years been an effective technique for the diagnosis and staging of lung cancer. Understanding the anatomy of mediastinal and hilar lymph nodes is essential to improve the yield of TBNA. Wang’s lymph node map is based on the lymph node map of the American Thoracic Society (ATS), and on the TBNA technique; it was published in 1994, and has promoted the development of both conventional TBNA (cTBNA) and endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA). In 2009, the International Association for the Study of Lung Cancer (IASLC) developed a new chest lymph node map to reconcile the differences between the Naruke and The Mountain-Dresler (MD)-ATS lymph node maps. The IASLC lymph node map was incorporated into the seventh edition of the tumor, node, metastasis (TNM) staging system for lung cancer, which directly affected the treatment and prognosis of lung cancer. There are significant differences between Wang’s lymph node map and the IASLC lymph node map in TNM staging, and it is imperative to understand these differences and correlate these maps for the prognosis and staging of lung cancer using cTBNA or EBUS-TBNA.